Femoral adipose tissue may accumulate the fat that has been recycled as VLDL and nonesterified fatty acids. - McQuaid, SE; Humphreys, S; Hodson, L; Fielding, B; Karpe, F; Frayn, K (2010)
OBJECTIVE: Gluteo-femoral, in contrast to abdominal, fat accumulation appears protective against diabetes and cardiovascular disease. Our objective was to test the hypothesis that this reflects differences in the ability of the two depots to sequester fatty acids, with gluteo-femoral fat acting as a longer-term "sink." RESEARCH DESIGN AND METHODS: A total of 12 healthy volunteers were studied after an overnight fast and after ingestion of a mixed meal. Blood samples were taken from veins draining subcutaneous femoral and abdominal fat and compared with arterialized blood samples. Stable isotope-labeled fatty acids were used to trace specific lipid fractions. In 36 subjects, adipose tissue blood flow in the two depots was monitored with (133)Xe. RESULTS: Blood flow increased in response to the meal in both depots, and these responses were correlated (r(s) = 0.44, P < 0.01). Nonesterified fatty acid (NEFA) release was suppressed after the meal in both depots; it was lower in femoral fat than in abdominal fat (P < 0.01). Plasma triacylglycerol (TG) extraction by femoral fat was also lower than that by abdominal fat (P = 0.05). Isotopic tracers showed that the difference was in chylomicron-TG extraction. VLDL-TG extraction and direct NEFA uptake were similar in the two depots. CONCLUSIONS: Femoral fat shows lower metabolic fluxes than subcutaneous abdominal fat, but differs in its relative preference for extracting fatty acids directly from the plasma NEFA and VLDL-TG pools compared with chylomicron-TG.